2014
DOI: 10.1080/00380768.2014.921579
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of drought tolerance in seedlings of sugar beet (Beta vulgarisL.) cultivars using inorganic and organic solutes accumulation criteria

Abstract: Drought is a major environmental factor limiting the production of crops. Drought tolerance of sugar beet (Beta vulgaris L.) cultivars in terms of growth and inorganic and organic solute accumulation was analyzed in this study. Four-week-old seedlings of three cultivars, "Gantang7", "SD13829" and "ST21916", differing in drought tolerance, were treated with different degrees of drought stress. Plant shoots and roots were harvested at 5 d after stress and subjected to analysis. Drought significantly reduced shoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 43 publications
1
24
1
Order By: Relevance
“…A key osmoprotective function of free proline was emphasized in numerous plants (Verbruggen and Hermans 2008, Szabados and Savouré 2010, Wu et al 2014. In addition to osmotic adjustment, proline has certain regulatory functions, acts as a signal molecule, and protects and stabilizes the structure of membranes and enzymes under environmental stress (Szabados and Savouré 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A key osmoprotective function of free proline was emphasized in numerous plants (Verbruggen and Hermans 2008, Szabados and Savouré 2010, Wu et al 2014. In addition to osmotic adjustment, proline has certain regulatory functions, acts as a signal molecule, and protects and stabilizes the structure of membranes and enzymes under environmental stress (Szabados and Savouré 2010).…”
Section: Discussionmentioning
confidence: 99%
“…reduced by drought stress in 4-week-old sugar beet seedlings, and their growth suffered largely from effect at osmotic stress of -1.0 MPa (Wu et al 2014). These results suggested that twomonth-old sugar beet plants display the drought tolerance to some extent, which can be due to increased ability for maintaining adequate water uptake by lateral root.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild beet was already used for sugar beet genetic improvement against pathogens (Panella and Lewellen, 2007). While its potential for improvement against abiotic factors has not yet been exploited, it has been proposed that the ability to accumulate compatible solutes is a breeding goal for abiotic stress tolerance (Bagatta et al, 2008; Ober and Rajabi, 2010; Wu et al, 2014), as well as the ability to accumulate Na + and K + (Abbasi et al, 2015). Europe is one of the most important centers for beet diversity (Maxted et al, 2008), the Iberian Peninsula being considered one center of origin of the Beta complex (OECD, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Physiological parameters such as relative water content, chlorophyll content have been used as key indicators of drought stress (Soltys-Kalina ., 2016;Ganji Arjenaki ., 2012;Mafakheri ., 2010;Arunyanark ., 2008). Furthermore, for observing metabolic responses to drought stress, proline and total reducing sugar contents are determined (Wu ., 2014;Naser ., 2010 Screening drought tolerant plants 509…”
Section: Introductionmentioning
confidence: 99%